Association of Patient Anthropometric Measurements and Dental Implant Treatment - Al-Radha ASD (Dove Medical Press, 2023)
Afya Sahib Diab Al-Radha Oral Surgery and Periodontology Department, College of Dentistry, Mustansiriyah University, Baghdad, IraqCorrespondence: Afya Sahib Diab Al-Radha, Oral Surgery and Periodontology Department, College of Dentistry, Mustansiriyah University, Central Baghdad Post Office, Post Box (P.O.) 55388, Baghdad, Iraq, Tel +9647816883387, Email drafya_diab@yahoo.com; drafya_diab@uomustansiriyah.edu.iqBackground: Dental implants are currently one of the most preferred treatment modalities for replacing missing teeth, as they are the most comparable to natural teeth. Even so, satisfaction with such treatment may differ depending on patient nature. The aim of this article was to examine the relationships between different anthropometric measurements on dental implant patient's satisfaction.Methods and Material: Self-administered questionnaire (structured questions) were given to patients who had dental implant treatment to evaluate their satisfaction level with dental-implant treatment. Different anthropometric measurements were taken: body height; weight; body mass index (BMI); body composition; waist/hip ratio; and circumferences at the waist, hip, and neck.Results: The overall BMI was 28.9± 4.7 kg/m2, there was a highly-significant difference in patient satisfaction among the different BMI groups (P< 0.000). The significant difference in most of those groups was between the obese group and the other groups. For neck circumference and waist/hip ratio, a significance difference between the normal weight and obese groups (P< 0.000) was found, while for percentage of muscle, the differences were between the overweight and obese groups (P< 0.000). According to BMI groups a highly significant difference in many patient satisfaction domains were found (P< 0.000). These significant differences were between the obese group and non-obese groups for most aspects of patient satisfaction. For patient satisfaction with final appearance, the normal BMI group differed significantly from the overweight BMI group (P=0.013). Additionally, for patient satisfaction with dentist performance and communication, the overweight BMI group showed significantly higher satisfaction than the normal BMI group (P=0.019). Body measurements were correlated negatively with overall patient satisfaction, and positively with satisfaction with prosthesis.Conclusion: The obese group patients had the lowest rate of patient satisfaction. BMI and other body measurements can be used to predict patient satisfaction with the outcome of dental implant treatment.Keywords: dental implant, obesity, body mass index, anthropometry